EFEKTIVITAS PROGRAM BANTUAN PANGAN NON TUNAI TERHADAP KESEJAHTERAAN MASYARAKAT DESA MADDENRA KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Syafruddin Syafruddin; Muhammad Ikbal; Azis Kalrah (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to determine the effectiveness of the non-cash food assistance program on the welfare of the community in Maddenra Village, Kulo District, Sidenreng Rappang Regency. The population of this study is 111 people (beneficiary families) while the sample size is 55 people (beneficiary families). Data collection techniques used in this study were observation, interviews, questionnaires and literature study. The data analysis technique used was validity test and data reliability test, and simple linear regression and hypothesis testing with the help of SPSS version 21 application. The results showed that the effectiveness of the Non-Cash Food Assistance Program in Maddenra Village with a percentage of 56% was in the poor category. Community welfare in Maddenra Village with a percentage of 58% is in the poor category. Based on the value of tcount > ttable or 3,305 > 2,008, then H0 is rejected and Ha is accepted, meaning that it has a significant effect of 17,6%, the magnitude of the effect of variable X on variable Y.